The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1002/pits.20027
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of listening and listening-while-reading accommodations on reading comprehension levels and rates in students with emotional disorders

Abstract: Researchers used alternating treatment designs to investigate the effects of listening-whilereading (LWR) and listening interventions on comprehension levels and rates in four middle school students with emotional disorders. During LWR, students were instructed to read passages silently along with experimenters. During the listening condition, we did not give students a printed copy of the passage but merely instructed them to listen as an experimenter read the passages aloud. The control condition consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 17 publications
1
62
0
Order By: Relevance
“…Acceptability measures confirmed these informal reports. If TELLS enhances comprehension only on text to which it is applied, then researchers should conduct comparison studies to determine if other previewing procedures (e.g., listening-while-reading) are more efficient and effective instructional strategies for enhancing comprehension on specific passages (see Hale et al, 2005, andWinn et al, 2006). The time spent engaged in TELLS, however, may be time well spent if TELLS causes meaningful increases in reading comprehension skills that enhance students' comprehension rates across texts.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Acceptability measures confirmed these informal reports. If TELLS enhances comprehension only on text to which it is applied, then researchers should conduct comparison studies to determine if other previewing procedures (e.g., listening-while-reading) are more efficient and effective instructional strategies for enhancing comprehension on specific passages (see Hale et al, 2005, andWinn et al, 2006). The time spent engaged in TELLS, however, may be time well spent if TELLS causes meaningful increases in reading comprehension skills that enhance students' comprehension rates across texts.…”
Section: Discussionmentioning
confidence: 96%
“…Researchers have shown that procedures designed to enhance oral reading speed or fluency (reinforcement, listening-while-reading, and repeated readings) also enhance reading comprehension rates (Freeland et al, 1999Hale et al, 2005;McDaniel et al, 2001;Skinner et al, 1993;Winn, Skinner, Oliver, Hale, & Ziegler, 2006). Researchers, however, have not used reading comprehension rate measures to evaluate procedures designed to enhance reading comprehension.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…There are several possible reasons for these intervention effects. First, research suggests that the LLP is an effective strategy to improve students' reading comprehension (Dowhower, 1987;Hale et al, 2005;Skinner et al, 1998). Listening passage from the researcher may have increased students' reading comprehension and improved comprehension probably contributed to the students' reading fluency.…”
Section: Discussionmentioning
confidence: 99%
“…In general, skill-based interventions are implemented as a single or combined strategy for improving reading fluency. One of the skill-based interventions, listening passage preview involves someone reading the passage to student while the student read silently (Hale, Skinner, Winn, Oliver, & Allin, & Molloy, 2005). Research have suggested that listening passage preview was effective on improving students' oral reading fluency (Daly & Martens, 1994;Daly, Martens, Hamler, Dool, & Eckert, 1999), accuracy (Daly, Martens, Dool, & Hintze, 1998), and comprehension levels (Dowhower, 1987;Skinner, Robinson, Adamson, Atchison, & Woodward, 1998).…”
Section: Introductionmentioning
confidence: 99%